New efficient network architecture BSN-MOT for parallel processing - Jiang-yun LI; Li-ting SUN (Tongxin xuebao)
BSN-MOT as a two-tier architecture that takes the advantages of both the BSN and the MOT was presented. Topological property and many communication and application algorithms are investigated. The communication algo-rithms include row-tree and column-tree broadcast, one to all broadcast, data sum, matrix multiplication, shortest path rooting and polynomial root finding. In contrast with other two similar tree-based two-tier architectures MMT and OM-ULT, the results show that the algorithms that run on BSN-MOT are much faster, and BSN-MOT is more competitive.